BBBP POLICY AS A HOLISTIC DEVELOPMENT OF THE NARENDRA MODI GOVERNMENT IN OPTIMISING WOMEN'S EMPOWERMENT IN INDIA 2015 - 2017 - Widyaputri, Primadiani Difida; putri, gustri eni (Jisiera: The Journal of Islamic Studies and International Relations, 2024)
Women empowerment is an attempt to provide power, choice and freedom for women to optimize their potential. At the national level, empowering women requires collective participation between the state as the highest political entity and society as the implementer of women empowerment. India, as a developing country in South Asia, is a country that is seeking to optimize women empowerment through holistic, multi-sector development policies that are capable of having a significant impact on the country's development. Under the leadership of Narendra Modi in his first term, a policy emerged called Beti Bachao Beti Padhao (BBBP) as a bridge in actualizing women's empowerment in India. The efforts contained in this policy are economic development through empowering abilities to increase economic growth (economically productive), providing guidance on women's participation in the public sphere, guaranteeing women's representation in the world of politics, as well as a culture of mainstreaming women in other sectors. Through the strategies made by Narendra Modi, women are given strength and guarantees from the state to fulfill their personal needs (self-sufficiency).